PEMERTAHANAN BAHASA MUNA DI KABUPATEN MUNA SULAWESI TENGGARA - Zalili Sailan (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe the maintenance of the Muna language in Muna Regency,Southeast Sulawesi. The data were collected using the ethnographic method by meansof observations and unstructured interviews. The analysis was referred to micro andmacrosociolinguistic theories. The findings are as follows. First, the population growthdoes not support the survival of the Muna language because of the increasing number ofmultiethnic newcomers. Second, the young generation’s mobility gives more space to theuse of Bahasa Indonesia. Third, the maintenance of the Muna Language is supported byelder people in villages but it is not supported by educated families, multiethnic families,elite groups, and school environments. Fourth, demographically, people aged 0 - 19 are notactive enough in using the Muna language, those aged 20 - 49 do not care about the useof the Muna language, and those aged 50 or more still use the Muna language actively.